Muropeptides and muropeptide transporters impact on host immune response - Maria Lucia Orsini Delgado; Joao Gamelas Magalhaes; Rachel Morra; Antonietta Cultrone (Gut Microbes)
In bacteria, the cell envelope is the key element surrounding and protecting the bacterial content from mechanical or osmotic damages. It allows the selective interchanges of solutes, ions, cellular debris, and drugs between the cellular compartments and the external environment, thanks to the presence of transmembrane proteins called transporters. The major component of the cell envelope is the peptidoglycan, consisting of long linear glycan strands cross-linked by short peptide stems. During cell growth or under stress conditions, peptidoglycan fragments, the muropeptides, are released by bacteria and recognized by the host Pattern Recognition Receptor, promoting the activation of their innate defense mechanisms. The review sums up the salient aspects of microbiota–host interaction with a focus on the NOD-dependent immune response to bacterial peptidoglycan and on the accountability of muropeptide transporters in the crosstalk with the host and in antibiotic resistance. Furthermore, it retraces the discoveries and applications of microorganisms-derived components such as vaccines or vaccine adjuvants.